Top-down processes derail bottom-up objectives: a study in community engagement and 'Slum-Free City Planning'. (13th September 2021) - Sanga, Naganika; Gonzalez Benson, Odessa; Josyula, Lakshmi
Abstract: Participatory processes in housing policies and planning that engage urban poor communities through grassroots networks have been widely celebrated, but scholars have also scrutinized these policies for their limitations on the ground. Such scholarship has primarily focused on outcome indicators and local implementation, relegating the state to the background. This study focuses on everyday practices rather than outcomes and on multi-level rather than local-level implementation, using India's national Slum-Free City Planning initiative, Rajiv Awas Yojana, in the mid-sized, southern city of Madurai as a case study. This paper draws from development studies literature to 'bring the state back in' to critically examine participatory planning with India's urban poor. Findings illustrate how community participation ideals are sacrificed by different players for procedural expediency and bureaucratic convenience. We suggest that the deprioritizing of community participation is not an isolated deviation from policy, but it is shaped by two structural impediments embedded within urban housing policy mechanisms: the lack of federal constitutional mandates for housing and, in their absence, the proliferation of time-bound and project-based conditional grants through national housing programmes for the urban poor. Together, they result in an arbitrary policy environment and a push-pull of power between different levels of government, thereby sidelining community participation objectives.